2022
DOI: 10.21037/tau-22-43
|View full text |Cite
|
Sign up to set email alerts
|

Overview of histologic variants of urothelial carcinoma: current trends and narrative review on treatment outcomes

Abstract: Background and Objective: The histologic variants of urothelial carcinoma (UC) are tumors arising from within the urothelium in which some component of the tumor morphology is other than urothelial.They are underdiagnosed, aggressive and have varying pathologic response rates to systemic chemotherapy.There are no consensus guidelines on the use of systemic chemotherapy in variant histology (VH) of UC. We performed a contemporary review on pathologic response rates to neoadjuvant systemic therapy and survival o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…14 In a recent narrative review, the use of NACT is recommended for pathologic downstaging, as a higher pathologic stage on surgery portends a worse survival outcome. 15 Based on this data, our patient was put on NACT, which was not beneficial in her case.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…14 In a recent narrative review, the use of NACT is recommended for pathologic downstaging, as a higher pathologic stage on surgery portends a worse survival outcome. 15 Based on this data, our patient was put on NACT, which was not beneficial in her case.…”
Section: Discussionmentioning
confidence: 95%
“…Hajiran and colleagues retrospectively reviewed 768 patients with clinical muscle invasive bladder cancer, 173 with variant histology, and reported that similar response rates were seen in all pathologies, and that both pure urothelial carcinoma and variant histology cohort demonstrated a survival benefit with this approach 14 . In a recent narrative review, the use of NACT is recommended for pathologic downstaging, as a higher pathologic stage on surgery portends a worse survival outcome 15 . Based on this data, our patient was put on NACT, which was not beneficial in her case.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary bladder urothelial carcinoma (UBUC) presents micropapillary sarcomatoid, squamous, and glandular variations. It is accessible to TUR (transurethral resection) and local chemotherapy; hence, it has a good prognosis [56][57][58].…”
Section: Urothelial Carcinoma (Uc)mentioning
confidence: 99%
“…Histologic variants of urothelial carcinoma comprise tumors arising from within the urothelium, in which some components of the tumor morphology are other than the urothelium ( Chalasani et al, 2009 ). The micropapillary, plasmacytoid, nested, and sarcomatoid histologic variants of urothelial carcinoma have been linked with poorer survival outcomes than conventional urothelial carcinomas and urothelial carcinomas with squamous or glandular differentiation, despite undergoing chemotherapy-induced downstaging ( Ogbue et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%